Teaching specialty subject’s improvement methodology - POLOTOVICH, MIRZOEV DILSHOD; QAHHOROVICH, QAHHOROV SIDDIQ (The journal of contemporary issues in business and government, 2021)
This article emphasizes that the clear formulation of teaching methods is a key factor in improving the quality of teaching. It was noted that the combination of state educational technologies with practical training on the basis of a clear plan will serve to improve the quality of education. Tariffs of foreign and domestic scientists on pedagogical technologies, comparative analysis of research work. The main purpose of the research is to completely get rid of the learning process from a homogeneous system, to process the technology. The main task of the research work is to train future teachers of engineering education using modern teaching methods and experience of their introduction into the educational process, to constantly improve their professional skills and to master effective innovative methods and implement them in practice. Independent work with advanced pedagogical technologies is guaranteed, along with independent work on the effective mastering of teaching materials within the framework of scientific programs. Because no one can achieve an agreed goal without independent action. It is therefore justified to consider independent activity as a means of learning and as a result. The source of students’ knowledge is not only the knowledge imparted in the teacher’s lectures, but also the student’s own perceptions and actions, and the teacher, in turn, should motivate the student to develop research skills, additional search skills. The main task of the article is to develop a new generation of state educational standards, curricula and scientific programs, to determine the qualification requirements, to introduce and develop energy education and to further improve this process. Based on the advanced technology education model, it is planned to develop students' creative skills by organizing new pedagogical games, using visual methods to explain practical topics, creating problem situations, organizing discussions, sharing students' ideas, increasing creative activity, forming independent thinking. The main novelty of the research is the pedagogical technology of teaching processes, organized in two traditional and non-traditional forms, and experimental work. The results of experimental work have shown on the basis of statistical analysis that the effectiveness of students' learning has increased.